2005
DOI: 10.1186/1476-4598-4-29
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks for diagnosis and survival prediction in colon cancer

Abstract: ANNs are nonlinear regression computational devices that have been used for over 45 years in classification and survival prediction in several biomedical systems, including colon cancer. Described in this article is the theory behind the three-layer free forward artificial neural networks with backpropagation error, which is widely used in biomedical fields, and a methodological approach to its application for cancer research, as exemplified by colon cancer. Review of the literature shows that applications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(73 citation statements)
references
References 50 publications
0
61
0
1
Order By: Relevance
“…ANNs are used to help physicians in disease diagnosis for the past five decades. NNs attracted especial attention due to their ability to learn complex issues, along with the ability to maintain accuracy, even in the absence of some information (22,23). Computational accuracy is an important tool used when applying an NN to ensure the quality of the final results (24).…”
Section: Discussionmentioning
confidence: 99%
“…ANNs are used to help physicians in disease diagnosis for the past five decades. NNs attracted especial attention due to their ability to learn complex issues, along with the ability to maintain accuracy, even in the absence of some information (22,23). Computational accuracy is an important tool used when applying an NN to ensure the quality of the final results (24).…”
Section: Discussionmentioning
confidence: 99%
“…SVMs provide a tool to overcome some of these limitations due to the theoretical principles upon which they are based [98]. An ANN approach utilizes all available data set to find ideal separating features and can also be used for classification [99] as has been reported for analysis of breast cancer [100] and hepatocellular carcinoma [101].…”
Section: Data Processing and Bioinformaticsmentioning
confidence: 99%
“…17 Ahmed's review showed that applications of ANNs have improved the accuracy of colon cancer classification and survival prediction compared to other mathematical or clinicopathological methods. 18 As a result, ANN appears to be an appropriate approach for modeling complex input-output relationships in medicine.…”
Section: Literaturementioning
confidence: 99%